Clinical outcomes of breast reconstruction using omental flaps: A systematic review - Jan Maerten Smit; Victor D. Plat; Marijn L.Q. van Est; Susanne van der Velde; Freek Daams; Vera L. Negenborn (JPRAS Open, 2024)
Background: Breast cancer is the most common cancer in women, and breast reconstruction improves the patient's quality of life. Autologous breast reconstruction provides benefits of natural appearance, feel, and long-term results without implant-associated problems. However, thin patients are not always suitable for standard autologous reconstructions. In these patients, an omental flap could be a useful alternative. The aim of this review was to provide an overview of the literature regarding the clinical outcomes of omental flaps in breast reconstruction. Methods: A systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using the Medline and Embase databases up to November 1, 2023. Study outcomes were type of flap, tissue transfer, cosmetic outcomes, and short- and long-term complications. Results: Eleven studies covering 985 reconstructions in 969 patients were included. The omentum was mostly laparoscopically harvested (88.6%) and a pedicled reconstruction was mostly performed (91.2%). The most commonly reported short-term complications were wound infections at the donor site (5.8%), partial flap necrosis, and fat necrosis. In the long term, epigastric, umbilical and tunnel hernias, and epigastric bulging were observed. Satisfactory cosmetic results were reported by the patients (88.7%) and professionals (80.0%). Conclusion: Breast reconstruction using an omental flap can be performed in unilateral reconstructions with acceptable donor-site morbidity if laparoscopically harvested. In general, satisfactory cosmetic outcomes were reported and it appears to be a suitable alternative for selected patients who prefer autologous, unilateral breast reconstruction. Further research is necessary to determine the ideal candidates for this reconstruction and the long-term effects of an omentectomy in young patients.